2018
DOI: 10.1177/2192568217747573
|View full text |Cite
|
Sign up to set email alerts
|

The Science and Clinical Applications of Placental Tissues in Spine Surgery

Abstract: Study Design:Narrative literature review.Objectives:Placental tissue, amniotic/chorionic membrane, and umbilical cord have seen a recent expansion in their clinical application in various fields of surgery. It is important for practicing surgeons to know the underlying science, especially as it relates to spine surgery, to understand the rationale and clinical indication, if any, for their usage.Methods:A literature search was performed using PubMed and MEDLINE databases to identify studies reporting the appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…The placenta is a temporary organ with a broad variety of unique physiological functions, as well as a distinctive structure and composition, which represent an immense potential for efficient application in the field of regenerative medicine [1][2][3][4][5][6][7][8][9]. The virtually unlimited availability of placental material along with highly pronounced therapeutic effects in a wide range of clinical cases provide support for the patients for over a century of successful clinical use and promote the further development of novel therapeutic strategies and approaches [3,[8][9][10][11][12][13][14][15]. In the majority of countries, the application of placental components faces no or low ethical issues.…”
Section: Introductionmentioning
confidence: 99%
“…The placenta is a temporary organ with a broad variety of unique physiological functions, as well as a distinctive structure and composition, which represent an immense potential for efficient application in the field of regenerative medicine [1][2][3][4][5][6][7][8][9]. The virtually unlimited availability of placental material along with highly pronounced therapeutic effects in a wide range of clinical cases provide support for the patients for over a century of successful clinical use and promote the further development of novel therapeutic strategies and approaches [3,[8][9][10][11][12][13][14][15]. In the majority of countries, the application of placental components faces no or low ethical issues.…”
Section: Introductionmentioning
confidence: 99%
“…45 More recently, there is early evidence to support its role in the treatment of a number of musculoskeletal pathologies, including the spine. 46 Notwithstanding, clinical research relating to amniotic membrane tissue in spinal surgery remains sparse. However, among the studies included in this analysis, very few complications have been reported suggesting the safety of amnion-derived products incorporated in spine procedures.…”
Section: Discussionmentioning
confidence: 99%
“…While this retrospective pilot study does not prove the superiority of dehydrated amnion over other dural adjuncts, or the efficacy of use, they demonstrate that it has an adequate safety profile with no complications directly related to its use in closures for craniotomies. They also report very low CSF leak rates and infection rates, particularly in craniotomies for infratentorial lesions [70][71][72].…”
Section: Neurosurgerymentioning
confidence: 95%